THE IMPLEMENTATION OF GUSDURIAN PASURUAN'S IPK IN INCREASING TOLERANCE VALUE IN RELIGIOUS PEOPLE IN SMA NEGERI 1 PURWOSARI, PASURUAN DISTRICT - Makruf Ahmad (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
One of the goals of the nation and state is to maintain the unity and integrity of the nation and to build a prosperous life together with all citizens and members of the religious community. As depicted in Pancasila, namely Bhinneka Tunggal Ika, although different but still one. However, it is not easy to achieve unity and integrity while still upholding differences and diversity. The obstacle that is quite severe to achieve unity and prosperity is the problem of national harmony, including inter-religious relations and the harmony of life for religious people. Seeing the current condition, it is very important to instill the value of tolerance at the school level, especially public schools, which are very easily influenced by intolerant narratives, even being entered by groups that spread hatred on behalf of God, then with such factors Gusdurian Pasuruan has carried out the Initiative to Prevent Violence (IPK), this program is a capacity building program for the CVE (Counter Violent Extremism) strategy in fighting the propaganda of extremist violence through strengthening partnerships with the community of SMA and SMK Negeri in Pasuruan Regency. This research uses qualitative methods because this research is in the form of descriptive data, in which this research was conducted by means of interviews with informants. Descriptive research is research that tries to describe an actual symptom, event, event. In other words, actual research is what it was when the research was carried out. Qualitative research has the following characteristics: (1) responsive, (2) flexible, (3) emphasizing wholeness, (4) based on expanding knowledge, (5) processing data as quickly as possible, (6) taking advantage of opportunities to clarify and retrieve conclusion, (7) take advantage of the opportunity to seek out unusual responses. Some of the things that Gusdurian Pasuruan did to achieve the goals of the IPK were as follows: 1) Identifying local dangers and signs of radicalism that lead to violence. 2) Develop positive counter-narrative and alternative content. 3) Build a cadre of intolerant local leaders. The results of this study included: 1) Ramadhan Peaceful Literacy, 2) Youth Cultural Discussion, 3) Koran Muharram with the theme: "Come on Hijrah... Become a Complete Muslim", 4) Film Discussion and Informal Meetings of District Toerance Ambassadors Pasuruan, 5) International Tolerance Day Short Video Competition